Do Language Examinations Influence How Teachers Teach - Philip Glover (Informascope, 2014)
Examination influence on teaching, known as washback, has been found on curriculum, materials and attitudes to teaching. Evidence of washback on how and why teachers teach, however, has proved harder to identify. This paper looks in detail at three complicating factors in washback research; the variety of terms used, conflicting findings and the nature of positive or negative washback. The paper describes a study that used discourse analysis in order to investigate examination influences on teacher talk. Findings suggest that washback on how teachers teach, if present, may lie in some categories of teacher talk but not in others.